(untitled) (International Journal of Food and Nutritional Sciences, 2022)
We give a summary of the most current developments in healthcare’s digitalisation and big data analytics. It is anticipated that these developments will play a significant role in the significant restructuring of the healthcare system in the future. We talk about the latest legislative efforts aimed at converting paper-based healthcare delivery procedures to electronic ones, with the intention of achieving better treatment outcomes. Cost pressure is a key force behind innovation in healthcare